Intraocular tuberculosis. (August 2012) - Bansal, Reema; Sharma, Aman; Gupta, Amod
Intraocular involvement by Mycobacterium tuberculosis is common in the absence of systemic evidence of tuberculosis. It can have protean manifestations with certain clinical signs that differentiate it from nontubercular causes of uveitis. Retinal vasculitis and serpiginous-like choroiditis have typical presentations. The diagnosis is usually presumptive and corroborated by laboratory tests such as positive tuberculin skin test or IFN-g release assays, or radiographic evidence on chest x-ray or PET/computer-assisted tomography. Definitive diagnosis by histopathological demonstration of mycobacteria is extremely rare, although PCR is increasingly being performed on intraocular samples. Antitubercular therapy effectively reduces the rate of recurrence of inflammation when administered in a timely manner along with corticosteroids.